The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1099/ijs.0.63550-0
|View full text |Cite
|
Sign up to set email alerts
|

Marinitoga hydrogenitolerans sp. nov., a novel member of the order Thermotogales isolated from a black smoker chimney on the Mid-Atlantic Ridge

Abstract: Marinitoga hydrogenitolerans sp. nov., a novel member of the order Thermotogales isolated from a black smoker chimney on the Mid-Atlantic Ridge A novel, thermophilic, anaerobic bacterium that is able to tolerate hydrogen was isolated from a deep-sea hydrothermal chimney collected at the Rainbow field on the Mid-Atlantic Ridge. Cells were rod-shaped and surrounded by a sheath-like outer structure (toga); they were weakly motile by means of a polar flagellum. They appeared singly, in pairs or in short chains. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…The Aquificaceae, Hydrogenothermaceae, and Desulfurobacteriaceae families of the Aquificales are observed principally in hydrothermal deposits and fluids. Additionally, isolated Aquificae organisms, including Thermodesulfobacterium hydrogeniphilum (251), a heterotrophic sulfate-reducing bacterium, and Thermodesulfatator indicus (385), an autotrophic sulfate-reducing bacterium, both of the Thermodesulfobacteria class, as well as Marinitoga hydrogenitolerans (450), an anaerobic organotroph of the Thermotogae class, appear to be environmentally relevant in hydrothermal environments.…”
Section: Taxonomy Of Dark Ocean Prokaryotic Microbial Communitiesmentioning
confidence: 99%
“…The Aquificaceae, Hydrogenothermaceae, and Desulfurobacteriaceae families of the Aquificales are observed principally in hydrothermal deposits and fluids. Additionally, isolated Aquificae organisms, including Thermodesulfobacterium hydrogeniphilum (251), a heterotrophic sulfate-reducing bacterium, and Thermodesulfatator indicus (385), an autotrophic sulfate-reducing bacterium, both of the Thermodesulfobacteria class, as well as Marinitoga hydrogenitolerans (450), an anaerobic organotroph of the Thermotogae class, appear to be environmentally relevant in hydrothermal environments.…”
Section: Taxonomy Of Dark Ocean Prokaryotic Microbial Communitiesmentioning
confidence: 99%
“…The species of the genus Petrotoga represent slightly thermophilic members of the generally hyperthermophilic and deep-branching bacteria of the order Thermotogales (2,3,31). Organisms of this genus have all been isolated from hot oilfield water (21,25), and have an optimum temperature for growth of 55 to 60°C in medium containing NaCl in the range of 0.5 to 10% (16).…”
mentioning
confidence: 99%
“…The quantity and diversity of sequences of members of the Thermotogales that have been detected in oil reservoirs suggest that these organisms may play important roles in these environments (Grassia et al, 1996;Li et al, 2006Li et al, , 2007Magot et al, 2000). While numerous species of the Thermotogales have been shown to grow very slowly at relatively low temperatures (30-40 u C) (Davey et al, 1993;Huber et al, 1989;Miranda-Tello et al, 2004;Nunoura et al, 2007;Postec et al, 2005), robust growth at these temperatures has not been observed with isolated strains. There is evidence from metagenomic studies that species of the Thermotogales with low optimal growth temperatures exist in nature (Nesbø et al, 2006).…”
mentioning
confidence: 99%